Investigation of Settlement on Repomix-B as Pothole Patching Material - MUDA, MOHAMAD NAEEM FAIEZ BIN MUDA; MOHD MASIRIN, MOHD IDRUS (Recent Trends in Civil Engineering and Built Environment, 2023)
The number of accidents on the roads and the money that is lost because of maintenance is becoming a big problem in Malaysia’s asphalt industry. Potholes are the most common problem with asphalt pavement. They need to be fixed right away to keep the pavement from getting worse and to cut down on the chances of accidents. This study was done to see how well five available cold mix asphalt products worked against the settlement compare to one hot mix asphalt. Eighteen kinds of patching materials that is nominated as sample A1, A2, A3, B1, B2, B3, C1, C2, C3, D1, D2, D3, E1, E2,E3, F1, F2 and F3 currently used in practice were tested in field. sample A is using Repomix base, sample B is using Hot Mix Asphalt base, sample C is using Repomix-B with 10% bentonite base, sample D is using Repomix-B with 20% bentonite base, sample E is using Repomix-B with 30% bentonite base and sample F is using Repomix-B with 40% bentonite base. In a summary, each samples comes out with three examples. The surveying, like levelling, was part of the test. The result from the test surveying indicates that the sedimentation for all samples. Based on how well each sample did, sample 3 is the best one to fight against settlement because the value of sediment is-0.001 and this sample reached the constant graph the earliest at 1050 passes. As a result, it is thought that sample Repomix-B with 40% is the best cold mix material for patching and maintenance work.